Management of in-stent restenosis after iliofemoral venous stenting - XU Huimin, GAO Hongxia (Waike lilun yu shijian)
Iliofemoral venous stent placement (IVS) is currently the first-line treatment for various acute and chronic deep vein obstruction diseases, effectively improving clinical symptoms in patients. However, in-stent restenosis (ISR) after IVS is a major cause of stent-occlusion issues and re-intervention. ISR is a complex pathophysiological process related to multiple risk factors, including preoperative stenosis severity, lesion characteristics, stent position, stent compression, inflow area of the stent, and other biomechanical factors. Currently, the management of ISR primarily involves balloon dilation, it is also essential to emphasize postoperative follow-up and monitoring, rational use of anticoagulant or antiplatelet medications, appropriate surgical indications, and choosing the right treatment method based on patient conditions. Laser ablation, intravascular endarterectomy devices, and radiation therapy may become new options for ISR treatment in the future.